2010
DOI: 10.1016/j.corsci.2010.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the long term benefits of Impressed Current Cathodic Protection

Abstract: This experimental field study interrupted the protection current offered by Impressed Current Cathodic Protection (ICCP) to ten in-service reinforced concrete structures. The study aimed to identify the long term effects of ICCP after it was recognised that some of the systems are now reaching the end of their design life and require a significant level of maintenance. It was found that after five or more years of ICCP, the steel remained passive for at least 24 months after interrupting the protection current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(78 citation statements)
references
References 14 publications
7
68
0
1
Order By: Relevance
“…In fact, more than 150 mV of ∆E decay was reached after 7 days (209 mV for EA, 211 mV for A and 153 mV for B). This efficiency of CP is similar to that obtained by Christodoulou et al [7]. However, this was not the case for EB.…”
Section: Application Of Cp Cprev and The Combined Treatments Ece+cp supporting
confidence: 78%
“…In fact, more than 150 mV of ∆E decay was reached after 7 days (209 mV for EA, 211 mV for A and 153 mV for B). This efficiency of CP is similar to that obtained by Christodoulou et al [7]. However, this was not the case for EB.…”
Section: Application Of Cp Cprev and The Combined Treatments Ece+cp supporting
confidence: 78%
“…In fact, more than 150 mV of ∆E decay was reached after seven days (209 mV for EA, 211 mV for A and 153 mV for B). This efficiency of CP is similar to that obtained by other researchers [10,42]. However, this was not the case for EB.…”
Section: Case Study 3: Ability Of the Gcp Anode System To Apply Cp Csupporting
confidence: 79%
“…This is supported by the Pitting Potential/Re-passivation Potential hypothesis [1]. By contrast, it has been suggested that modifying the surface of the steel by raising the pH is the dominant protective effect, with reports that typical Impressed Current Cathodic Protection current densities are enough to halt corrosion when applied for long periods [2,3], or delay its onset in aggressive environments once the protective current has been removed [4,5]. These observations support the basis of the Pit Re-alkalisation/pH Maintenance hypothesis [6][7][8].…”
Section: Introductionmentioning
confidence: 67%